MANAJEMEN KOMPETENSI GURU NEGERI OLEH DINAS PENDIDIKAN KABUPATEN HALMAHERA TIMUR - Subhan Hayun; Rustam Hasyim (Universitas Khairun, 2018)
Abstract. This research was conducted to describe teachers’ competence,the teachers’ competence is one of the influence factor in education success, teacher’s competence to cover: (1) pedagogic competence, (2) personal competence, (3) professional competence and (4) social competence.This research also studied the concepts of the teachers’ competence, the factors influence in teacher’s competence, the strategy of teachers’ competence, and good management in teachers’ competence. These researches were used qualitative approach. The data sources were consist of the head master, teacher and parents. The data were collected by observation, in-depth interview, and documentation. The obtained data were verified and analyzed through data verified, data reduction continued to take conclusion.The findings of the research are: (1) the distribution of teacher inthe environment of Provincial Office of Education, Youth and Sport of East Halmahera Regency is not good and, (2) The competences of teachers in the elementary schools must be upgraded to fulfill the standard of competence and (3) The development programs of teacher’ competence in the elementaryschools were also not good. Key Word: teachers’ distribution, the developing teacher’s competence, the systematization of management teacher’s competence